(untitled) (Research, Society and Development, 2022)
Inflammatory and oxidizing factors are important for the triggering of diseases such as arthritis, lupus, and currently, the serious effects of coronavirus disease (COVID-19), which has an increase in inflammatory factors during its development and, consequently, can be mitigated by the beneficial effects of Baccharis dracunculifolia (Bd) and Brazilian Green Propolis (BGP). A literature search through PubMed, ResearchGate and HOLLIS Harvard Library Online Catalog was performed from the date of inception until 01/07/2021. A combination of the following keywords was used: propolis and baccharis dracunculifolia, anti-inflammatory, antioxidant and immunomodulation. The results of inflammatory and oxidizing factors shown by the study are important for the medical field, in addition to understanding how there are numerous compounds that are not yet known and mainly due to their possible treatments for various diseases. We conclude that BD and BGP are important for the reduction of inflammatory and oxidizing factors, which can be beneficial in immunological diseases and in exorbitant inflammatory factors as observed in COVID-19.